A chaotic image encryption scheme based on multi-directional confusion and diffusion operations. (November 2022) - Hussain, Muhammad; Iqbal, Nadeem; Bashir, Zia
Abstract: A careful perusal of the literature regarding the image encryption algorithms indicates that many research articles based on pixel swapping operations in the horizontal and vertical orientations, have been published. This study ventures to develop a yet another sophisticated algorithm by extending the swapping operations along the diagonal–antidiagonal directions. Besides, unlike the previous studies, the confusion and diffusion operations over the pixels of the given input plain image have been crafted in a parallel fashion. This work has employed a 4D chaotic system to spawn the streams of random numbers. The initial values and the system parameters have been made dependent over the given plain image in order to inject the plaintext sensitivity in the proposed cipher. As a modus operandi of the proposed encryption algorithm, a non-intersecting pair of row and column is selected randomly with the same arbitrary length and swapped/XORed according to the value dictated by the random numbers. The same operations have been carried out for the non-intersecting pair of diagonal and anti-diagonal. The reason for selecting the non-intersecting pair stems from the fact that intersecting pairs cause to lose the precious pixels data which questions the potential invertibility feature of the proposed algorithm. To demonstrate the improved efficiency, ability to withstand the varied attacks by the cryptanalysis savvy, and prospects for some real-world application, the algorithm has been subjected to a comprehensive set of evaluation metrics.